Case Report: Chronic Lymphocytic Leukemia With a Rare Translocation t(14;19)(q32;q13) Involving IGH/BCL3 Rearrangements: Report of Three Chinese Cases and Literature Review - Li, Qinlu; Xing, Shugang; Zhang, Heng; Mao, Xia; Xiao, Min; Wei, Jia; Wang, Ying (Frontiers in Oncology, 2020)
Background: a translocation t(14;19)(q32;q13) leading to a fusion of IGH and BCL3 which is a rare cytogenetic abnormality in CLL patients, has a more aggressive clinical course with a shorter time to first treatment (TTT) and worse overall survival (OS). To date, there is no literature reporting the identification of the t(14;19) in Chinese CLL patients and the reviewing the characteristic of all patients with this abnormality reported previously in the literature. Patients and Methods: We first demonstrate three cases of t(14; 19) translocation among the 200 CLL patients from 2017 to 2019 in our hospital. We investigated several aspects such as clinicopathologic features, cytogenetic analysis, IGHV mutations, next-generation sequencing technology (NGS), and histopathological characteristics in order to clearly define the features of this entity in Chinese patients and compare them with patients reported previously in western countries. Results: .The clinical and pathological features of our three cases resemble those of earlier reports. All patients had atypical morphologic features and atypical immunophenotypes with low CLL scores dectected by flow cytometry. All cases were unmutated in the IGHV mutations. Two cases showed complex karyotype and one case demonstrate missense mutations of TP53 and FBXW7. Conclusion: In conclusion, this is the first report on IGH/BCL3-positive B-CLLs in Chinese people, which provided a comprehensive analysis of clinical and pathological characteristics. In addition to some similar clinical and laboratory features reported in the previous literature, we first found that CLL with t(14;19) has a higher possibility of being accompanied with high complex karyotype (high-CK), which is now regarded as a novel negative prognostic marker. Early identification of this abnormality in CLL patients is so important that patients can benefit from the more aggressive treatments at the onset of the disease.